Chemoentrepreneurship Based Student Worksheet Development to Improve Enterprise Interest in Chemical Teachers - Afrida Ekayanti; Asmadi M Noer; Roza Linda (Journal of Educational Sciences, 2021)
The purpose of this study was the development of a chemoentrepreneurship based student worksheet (LKM) to increase the entrepreneurial interest in chemistry teacher candidates. The sample of this study was 115 students of the Department of Chemistry at the University of Riau and the State Islamic University (UIN) Sultan Syarif Kasim in the 6th semester of the 2019 academic year. The results obtained at the validation stage of MFI development were 95% with the valid category. The results of the small-scale test on the one-one test obtained an average percentage of 84.80% which was included in the very practical category. Furthermore, the lecturer response obtained an average percentage of assessment of 90.40% with the LKM category being well used in the learning process. The results of the small-scale trial assessment obtained an average percentage of the assessment of 85.16% which falls into the very practical category. The results of large-scale student assessments after using the LKM developed through filling out the student response questionnaires obtained an average score percentage of 80.63% with the practical category. The results of the increase in the entrepreneurial interest of UR students as a whole were 80.61, including the high category, and the results of the UIN students' interest in entrepreneurship as a whole were 81.64 including the very high category.